Exploratory Study of Student Needs in the Development of Technology-Based Chemical Computing Software - Ariyatun Ariyatun; Sylva Sagita; Devita Marlina Venessa; Vida Zenitha Sudariasri; Novi Andri Nurcahyono; Rosi Fitri Ramadani (Universitas Negeri Yogyakarta, 2026)
The development of digital technology in education demands innovations in chemistry learning, especially in explaining abstract concepts such as molecular structure, chemical reactions, and properties of compounds. This research aims to explore the needs of chemistry education students towards the development of technology-based chemical computing software. The research method uses a quantitative approach with an exploratory descriptive design. The data was obtained through a closed questionnaire on the Likert scale, which was distributed to 117 students of the Chemistry Education study program from three universities in Indonesia. Data analysis was carried out using descriptive statistics in the form of frequency, average, and standard deviation. The results showed that students had a high need for interactive 3D molecular visualization features (M = 4.09), integration of materials with concept animation (M = 4.09), and interactive exercises (M = 4.06). In addition, simple reaction simulation features and auto-scoring were also considered important (M = 4.03). Meanwhile, the aspect of cross-device access (M = 3.76) and the availability of Indonesian content according to the national curriculum (M = 3.55) received a lower score, although it remained in the high category. The conclusion of this study emphasizes the importance of developing chemical computing software that is not only visual, but also educational, adaptive, and according to the needs of students. The implications of the research results provide direction for educational technology developers, curriculum designers, and higher education institutions in designing chemistry learning media that are more contextual, inclusive, and sustainable.